Band Ligation VersusGlue Injection for Bleeding Gastric Varices - Muhammad Faheem , Muhammad Khurram , Saima Ambreen , Muhammad Arif , Waseem Amjad , Rahim Iqbal , Arshad Iqbal Satti, Muhammad Faheem , Muhammad Khurram , Saima Ambreen , Muhammad Arif , Waseem Amjad , Rahim Iqbal , Arshad Iqbal Satti (Journal of Rawalpindi Medical College, 2017)
Background : To compare endoscopic variceal sclerotherapy with N-butyl-2-cyanoacrylate- Histoacryl (EVS) and endoscopic variceal band ligation (EBL) for treatment of bleeding gastric varices (GV). Methods: In this randomized control trial 140 patients with bleeding gastric varices were included.Bleeding GV patients diagnosed endoscoically were treated with EVS or EBL in two equal groups after randomization. Bleeding control or otherwise was confirmed during the procedure. Patients were followed for 1 month for re-bleeding. Comparison of the patients undergoing EVS or EBL was done in terms of bleeding control and re-bleeding during follow up period. Chi2 test was used to seek statistically significant association in this regard. Results: Endoscopic bleeding control was confirmed in all except 1 of EBL patients who expired. 4 (5.7%) of EVS 10 (14.28%) EBL patients had re-bleeding (P >0.05). Conclusion: EVS and EBL are comparative procedures for treatment ofbleeding GV for control of active bleeding and re-bleeding over one month follow up.